Molecular and cellular characterization of immunity conferred by lactobacilli against necrotic enteritis in chickens - Alizadeh, Mohammadali; Shojadoost, Bahram; Boodhoo, Nitish; Raj, Sugandha; Sharif, Shayan (Frontiers in Immunology, 2023)
Necrotic enteritis is an important enteric disease of poultry that can be controlled with in-feed antibiotics. However, with the concerns over antimicrobial resistance, there is an increased interest in the use of alternatives. Probiotics are one of the alternatives that have gained considerable attention due to their antimicrobial and immunomodulatory activities. Therefore, in the present study, we evaluated the effects of two different Lactobacillus species alone or as a cocktail on prevention of necrotic enteritis. Day-old male broiler chickens were divided into five groups and on days 1, 8, 15, and 22, birds in groups 2 and 3 received 1×108 colony forming units (CFU) of L. johnsonii and L. reuteri, respectively. Group 4 received probiotic cocktails containing both bacteria (108 CFU/bird) and the negative and positive control groups did not receive any lactobacilli. Starting on day 23 post-hatch, birds in all groups (except the negative control group) were orally challenged twice per day with 3×108 CFU of a pathogenic C. perfringens strain for 3 days. Tissue and cecal samples were collected before and after challenge to assess gene expression, lymphocyte subsets determination, and microbiome analysis. On day 26 of age, lesion scoring was performed. The results demonstrated that the group that received the lactobacilli cocktail had significantly reduced lesion scores compared to the positive control group. In addition, the expression of interleukin (IL)-12 in the jejunum and CXC motif chemokine ligand 8 (CXCL8), IL-13, and IL-17 in the ileum were downregulated in the group that received the lactobacilli cocktail when compared to the positive control. Treating chickens with the lactobacilli cocktail prior to challenge enhanced the percentage of CD3-CD8+ cells and Bu-1+IgY+ B cells in the ileum and increased the frequency of monocyte/macrophages, CD3-CD8+ cells, Bu-1+IgM+, and Bu-1+IgY+ B cells in the jejunum. Treatment with the lactobacilli cocktail reduced the relative expression of Gamma-Protobacteria and Firmicutes compared to the positive control group. In conclusion, the results presented here suggest that treatment with the lactobacilli cocktail containing L. johnsonii and L. reuteri reduced necrotic enteritis lesions in the small intestine of chickens, possibly through the modulation of immune responses.